2022
DOI: 10.1039/d2ea00041e
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and human health risks of atmospheric microplastics (MPs): a review

Abstract: Microplastics (MPs) in the atmosphere are ubiquitous and persistent emerging pollutants, which have been an environmental issue of global concern. This overview summarizes the sources, morphological size and compositional characteristics,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 193 publications
1
11
0
Order By: Relevance
“…4 However, a much clearer understanding of the levels present with improved standardised methods was required before risks could be assessed. Recent work on inhalation (see, for example, Yang et al 2021;Yao et al 2022;Guanglong et al 2023) found that urban areas could contain high concentrations outside from sources such as textiles and vehicle tyres, brakes, etc., but the concentration of microplastic particles indoors tended to be higher from textiles, furniture, building materials, and human activities. A significant potential pathway for micro-and nanoplastics is to enter the lungs along the trachea, pass into the blood vessels through migration, and then spread through the circulatory system so that a wide range of cells, tissues, organs, and systems could be exposed.…”
Section: Extended Producer Responsibilitymentioning
confidence: 99%
“…4 However, a much clearer understanding of the levels present with improved standardised methods was required before risks could be assessed. Recent work on inhalation (see, for example, Yang et al 2021;Yao et al 2022;Guanglong et al 2023) found that urban areas could contain high concentrations outside from sources such as textiles and vehicle tyres, brakes, etc., but the concentration of microplastic particles indoors tended to be higher from textiles, furniture, building materials, and human activities. A significant potential pathway for micro-and nanoplastics is to enter the lungs along the trachea, pass into the blood vessels through migration, and then spread through the circulatory system so that a wide range of cells, tissues, organs, and systems could be exposed.…”
Section: Extended Producer Responsibilitymentioning
confidence: 99%
“…Microplastics, plastic pieces smaller than 5 mm, could be a global environmental threat due to their worldwide presence and potential risks to ecosystems and human health. , By 2019, global plastic production reached 368 million tons, with roughly 60% of the waste material ending up in landfills or the natural environment . Among discarded plastics, ∼6.5–27% are microplastics .…”
Section: Introductionmentioning
confidence: 99%
“…This ubiquity of MPs in the atmosphere means that humans are potentially at risk. Humans can be exposed to MPs through inhalation, ingestion, and dermal contact, with potential consequences such as lung inflammation, immune and metabolic issues, DNA damage, and oxidative stress, causing issues in the respiratory, digestive, immune, reproductive, and nervous systems [31][32][33][34][35]. All of these health risks show the urgency of increasing our knowledge about the level of airborne MPs.…”
Section: Introductionmentioning
confidence: 99%
“…reproductive, and nervous systems [31][32][33][34][35]. All of these health risks show the urgency of increasing our knowledge about the level of airborne MPs.…”
Section: Introductionmentioning
confidence: 99%